PERAN ORANG TUA DALAM PENGEMBANGAN SOSIAL EMOSIONAL ANAK DI ERA SOCIETY 5.0 - Puspita, Shinta Mutiara; Maulani, Susan; Narita, Ainun (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2024)
The Society   5.0 era is a concept of a human-centered and technology-based Society  , where early childhood is also very close to technology, especially gadgets. This has more or less affected the social emotional development of early childhood. This study aims to determine the role of parents in the development of children's social emotional aspects in the Society   5.0 era and to determine the social emotional aspects of children in the Society   5.0 era using a qualitative descriptive approach to parents who have children aged 4-5 years. Data collection techniques with interviews and observations. The role of parents in the Society   5.0 era has a very influential role in children, differences in children's behavior were found when using technology and their social emotions in parents who play a direct role in children and parents who work and the social emotional aspects of children are currently influenced by the Society   5.0 era which makes children dependent on gadgets so that children are more comfortable alone with gadgets which has an impact on minimal interaction and socializing children with others. The role of parents is very influential in the social emotional development of early childhood, therefore the need for care and guidance for children.